Perspective: Humanized Pig Models of Bladder Cancer - Segatto, Natália Vieira; Bender, Camila Bonemann; Seixas, Fabiana Kommling; Schachtschneider, Kyle; Schook, Lawrence; Robertson, Noah; Qazi, Aisha; Carlino, Maximillian; Jordan, Luke; Bolt, Courtni; Collares, Tiago (Frontiers in Molecular Biosciences, 2021)
Bladder cancer (BC) is the tenth most common neoplasia worldwide and holds expensive treatment costs due to its high recurrence rates, resistance to therapy and the need for lifelong surveillance. Thus, it is necessary to improve the current therapy options and identify more effective treatments for BC. Biological models capable of recapitulating the characteristics of human BC pathology are essential in evaluating the effectiveness of new therapies. Currently, the most commonly used BC models are experimentally-induced murine models and spontaneous canine models, which are either insufficient due to their small size and inability to translate results to clinical basis (murine models) or rarely spontaneously observed BC (canine models). Pigs represent a potentially useful animal for the development of personalized tumors due to their size, anatomy, physiology, metabolism, immunity, and genetics similar to humans and the ability to experimentally induce tumors. Pigs have emerged as suitable biomedical models for several human diseases. In this sense, the present perspective focuses on the genetic basis for BC; presents current BC animal models available along with their limitations; and proposes the pig as an adequate animal to develop humanized large animal models of BC. Genetic alterations commonly found in human BC can be explored to create genetically defined porcine models, including the BC driver mutations observed in the FGFR3, PIK3CA, PTEN, RB1, HRAS, and TP53 genes. The development of such robust models for BC has great value in the study of pathology and the screening of new therapeutic and diagnostic approaches to the disease.